A renewable composite adsorbent for removing iron from amino acid mother liquor, a preparation method thereof and an application method thereof
Patent Information
- Application Number
- CN202611465745.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
化学沉淀法容易产生含铁污泥,并可能造成目标氨基酸共沉淀损失;氧化还原法可能引入氧化剂残留;纳滤、反渗透等膜分离方法存在膜污染和运行成本较高的问题
(1)通过在D418型树脂孔道中引入羧甲基壳聚糖、支化聚乙烯亚胺、单宁酸及硅氧组分,构建包含膦酸基、氨基、羧基和酚羟基的多类型配位位点的改性树脂,并与D418型树脂、大孔丙烯酸酯系中极性吸附树脂及酸洗椰壳颗粒活性炭复配,有利于吸附氨基酸母液中不同形态的铁离子,同时有效吸附色素分子,实现深度除铁与脱色的双重效果。
Abstract
Description
Technical Field
[0001] This application relates to the fields of biochemical engineering and adsorption separation technology, specifically to a renewable composite adsorbent for iron removal from amino acid mother liquor, its preparation method, and its application method. Background Technology
[0002] Amino acid mother liquor is an amino acid-containing solution formed during amino acid fermentation and protein hydrolysis, typically with a high total free amino acid mass fraction. During amino acid fermentation and protein acid hydrolysis, factors such as equipment corrosion, raw material contamination, and process water use can lead to iron ion enrichment in the solution. The presence of iron ions adversely affects the color, stability, and recovery rate of amino acid products.
[0003] Currently, commonly used industrial iron removal methods include chemical precipitation, oxidation-reduction, membrane separation, and adsorption. Chemical precipitation easily produces iron-containing sludge and may cause the loss of target amino acids through co-precipitation; oxidation-reduction may introduce oxidant residues; membrane separation methods such as nanofiltration and reverse osmosis suffer from membrane fouling and high operating costs. Adsorption methods have the advantages of mild operating conditions, relatively simple equipment, and ease of continuous operation, but ordinary activated carbon or macroporous adsorption resins have limited selectivity for complex iron ions, resulting in limited iron removal depth and poor effect on improving solution color.
[0004] Therefore, it is of great significance to develop an adsorbent that can efficiently remove iron ions in various forms from amino acid mother liquor and has good regeneration performance. Summary of the Invention
[0005] To address the aforementioned issues, this application provides a regenerable composite adsorbent for iron removal from amino acid mother liquor, its preparation method, and its application method. The regenerable composite adsorbent is prepared by using a modified resin as the main iron-binding material, combined with D418 type resin, a macroporous acrylate-based polar adsorption resin, and acid-washed coconut shell granular activated carbon. When used, it is combined with microfiltration pretreatment, upward fixed-bed adsorption, and acid-alkali washing regeneration, thereby improving the adsorbent's iron removal function and reusability in amino acid solutions.
[0006] The first aspect of this application provides a regenerable composite adsorbent for iron removal from amino acid mother liquor. Based on dry weight, the regenerable composite adsorbent comprises 74-86 parts of modified resin, 8-14 parts of D418 type resin, 4-8 parts of macroporous acrylate-based polar adsorption resin, and 2-4 parts of acid-washed coconut shell granular activated carbon, with the sum of the dry weight of each component being 100 parts. The preparation method of the modified resin includes the following steps: S1, mixing γ-glycidyl etheroxypropyltrimethoxysilane, ethanol, and water, adjusting the pH to 4.3-4.8, and hydrolyzing under stirring to obtain a silane hydrolysate; S2, dissolving carboxymethyl chitosan in water, adding branched polyethyleneimine and silica sol, stirring, and then adding the silane hydrolysate, adjusting the pH to 6.0-6.8 to obtain a pore impregnation precursor solution; S3, adding D418 type resin to the pore impregnation precursor solution, and applying pressure at -0.085 to -0.065 MPa. S3. Maintain the pressure under the given conditions for 25–40 min, then restore to atmospheric pressure and maintain the pressure under atmospheric pressure for 30–60 min; S4. Disperse tannic acid in water to obtain an aqueous tannic acid solution, add the aqueous tannic acid solution to the system obtained in step S3, maintain the pressure under the conditions of -0.080 to -0.060 MPa for 15–30 min, restore to atmospheric pressure, adjust the pH to 8.0–8.6, and place it in a sealed reaction vessel, reacting at 52–58°C for 5–8 h; S5. After the reaction is completed, filter under reduced pressure to obtain resin particles, wash with water and vacuum dry to a water content of 45%–58%, to obtain the modified resin.
[0007] D418 resin possesses a rigid three-dimensional network structure and internally interconnected channels. The oxygen atom on its functional group, aminomethylenephosphonic acid (-NHCH2PO3Na2), can act as a coordinating atom with Fe. 3+ It forms stable five-membered ring chelates, which can be used for iron removal from amino acid mother liquor, but it is not effective against Fe. 2+Iron-amino acid complexes, iron-peptide complexes, and organic pigments have relatively weak coordination abilities, and their iron removal depth remains limited when used alone. The applicant's research found that using D418 resin as a carrier matrix, in-situ composites of silica sol / silane coupling agent, carboxymethyl chitosan, branched polyethyleneimine, and tannic acid network within the interconnected channels of the D418 resin can reduce the iron ion content in the amino acid mother liquor and improve the solution color. Specifically, step S1 hydrolyzes γ-glycidoxypropyltrimethoxysilane at pH 4.3–4.8 to generate silanol groups, which is beneficial for generating siloxane polymers with moderate chain lengths and maintained epoxy group reactivity, providing a foundation for the subsequent formation of fixed and continuous silicon-oxygen inorganic and organic networks within the channels; step S3 ensures sufficient contact between the D418 resin and the channel impregnation precursor solution under vacuum-atmospheric pressure conversion conditions, facilitating the full entry of the modified components into the resin channels; step S4 adds tannic acid solution to the pre-impregnated solution... In the system after vacuum impregnation, a second vacuum treatment is performed to facilitate the entry of tannic acid into the resin pores and its full contact with carboxymethyl chitosan, branched polyethyleneimine, silica sol, and silane hydrolysates. This avoids the inability of tannic acid and branched polyethyleneimine to form insoluble flocculent precipitates due to electrostatic bonding in solution when added together with other modified components in step S3, which would prevent the modified components from fully entering the pores. Adjusting the pH of the system to 8.0–8.6 and reacting in a closed reaction vessel allows the hydrolyzed silane in the pores to react with the silica sol. The resin undergoes a condensation reaction to form a silicon-oxygen inorganic network. The epoxy groups of the silane can undergo a ring-opening reaction with the amino groups contained in D418 resin, carboxymethyl chitosan, and branched polyethyleneimine to form β-hydroxypropylamine bonds. The silicon-oxygen network and tannic acid can interact with carboxymethyl chitosan and branched polyethyleneimine through hydrogen bonds, thereby forming a network structure with a large cross-linking span and stable structure with nanoparticles as the framework in the internal channels of D418 resin. This is achieved by utilizing the carboxyl groups and primary amine groups on carboxymethyl chitosan, the primary and secondary amine groups on branched polyethyleneimine, and monoamine groups. The phenolic hydroxyl groups on nitric acid enhance the coordination ability for iron ions of different valence states and their complexes, while also exhibiting good amino acid recovery rate and good regeneration and reuse performance. Step S5 removes insufficiently fixed free components and residual acid and alkali substances from the surface and pores of the resin particles through vacuum filtration and water washing. Then, moderate dehydration is performed using vacuum drying to maintain the modified resin in a suitable wet swelling state and pore connectivity, avoiding excessive dehydration that could lead to pore structure collapse and network breakage of the modified components, thus deteriorating the adsorption function of the modified resin. A composite adsorbent is obtained by compounding the modified resin with D418 type resin, macroporous acrylate-based polar adsorption resin, and acid-washed coconut shell granular activated carbon. D418 type resin can adsorb Fe... 3+To achieve high-throughput rapid adsorption, macroporous acrylate resins can remove organic pigments and iron-organic complexes through physical adsorption, while acid-washed coconut shell granular activated carbon is beneficial for further deep decolorization. The combination of the three helps to reduce the organic load of the modified resin, maintain the long-term availability of the coordination sites of the modified resin, and has mature regenerability, making the composite adsorbent further have excellent iron removal, decolorization, and regeneration and reuse performance.
[0008] In any embodiment, the preparation of the modified resin includes the following steps: S1, mixing 2-4 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 10-18 parts of ethanol, and 15%-25% of the total amount of added deionized water, adjusting the pH of the mixture to 4.3-4.8 using an acetic acid aqueous solution with a mass fraction of 8-12%, and hydrolyzing by stirring at 28-35°C and 300-500 r / min for 35-50 min to obtain a silane hydrolysate; S2, adding 6-10 parts of carboxymethyl chitosan to 45%-55% of the total amount of added deionized water, and stirring at 35-45°C and 500-800 r / min. Stirring under the specified conditions for 40–70 min, add 2–4 parts of branched polyethyleneimine and 6–10 parts of silica sol (based on dry silica), continue stirring for 20–40 min, then add the silane hydrolysate prepared in step S1, and adjust the pH of the system to 6.0–6.8 using an 8–12% sodium hydroxide aqueous solution to obtain the pore impregnation precursor solution; S3, add 100 parts of D418 type resin (based on dry basis) to the pore impregnation precursor solution, adjust the vacuum degree in the reaction vessel to -0.085–-0.065 MPa at 20–30 °C and maintain it for 25–40 min, then... Then restore to normal pressure and maintain at normal pressure for 30-60 min; S4, dissolve 2-4 parts of tannic acid in the remaining deionized water to form an aqueous tannic acid solution, add the aqueous tannic acid solution to the system obtained in step S3, maintain at a vacuum of -0.080 to -0.060 MPa for 15-30 min, restore to normal pressure, adjust the pH of the system to 8.0-8.6 using a 10% sodium hydroxide aqueous solution, place the pH-adjusted system in a sealed reaction vessel, and react at 52-58℃ and 150-300 r / min for 5-8 h; S5, after the reaction is completed, reduce... Resin particles were obtained by pressure filtration and transferred to a washing column. The particles were washed with deionized water at a flow rate of 2–4 BV / h until the pH of the washing solution was 6.5–7.5 and the absorbance of the washing solution at 280 nm was no greater than 0.05. The washed resin particles were then vacuum dried at 40–50 °C and a vacuum degree of -0.080–-0.060 MPa until the water content of the resin particles was 45%–58%, thus obtaining the modified resin. The total amount of deionized water used was 220–320 parts, excluding the water contained in the silica sol, acetic acid aqueous solution, and sodium hydroxide aqueous solution.
[0009] The above-mentioned preparation process of modified resin is beneficial for further capturing iron ions in different forms and maintaining stable iron removal performance.
[0010] Here, "BV" refers to "Bed Volume", which is the static bed volume formed by the corresponding wet resin, adsorbent material or composite adsorbent in a state without liquid flow.
[0011] In any embodiment, the matrix of the D418 resin is a styrene-divinylbenzene crosslinked copolymer, and the functional group is -NHCH2PO3Na2; the wet particle size of the D418 resin is 0.315-1.25 mm, the water content is 55%-60%, and the wet volume exchange capacity is expressed as Ca... 2+ The following parameters are required: a wet true density of 1.10–1.18 g / mL and a sphericity of 90% after grinding; a wet particle size of 0.40–1.00 mm, a specific surface area of 350–600 m² / g, and an average pore size of 8–25 nm for the macroporous acrylate polar adsorption resin; a particle size of 0.45–1.20 mm, an iodine adsorption value of 900 mg / g, an ash content of 3.0% and an iron content of 0.02%; a degree of carboxymethyl substitution of 0.65–0.95 and a degree of deacetylation of 80%–95% for carboxymethyl chitosan; a weight-average molecular weight of 10,000–30,000 for branched polyethyleneimine; and a silica content of 25%–35% and a silica particle size of 8–25 nm for silica sol.
[0012] D418 type resin uses styrene-divinylbenzene crosslinked copolymer as the matrix, with a wet particle size of 0.315–1.25 mm and a water content of 55%–60%. The wet volume exchange capacity is expressed as Ca²⁺. 2+ The wet true density is not less than 0.35 mmol / mL, and the sphericity after grinding is not less than 1.10–1.18 g / mL. The sphericity after grinding is not less than 90%, which is conducive to giving the resin suitable channels, phosphonic acid group coordination capacity and mechanical strength, thereby meeting the requirements of vacuum impregnation, fixed bed packing and repeated acid and alkali regeneration. The wet particle size of the polar adsorption resin in the macroporous acrylate system is 0.40–1.00 mm, the specific surface area is 350–600 m² / g, and the average pore size is 8–25 nm, which is conducive to adsorbing organic pigments, some macromolecular organic matter and iron-organic complexes in amino acid mother liquor. The particle size of the acid-washed coconut shell granular activated carbon is 0.45–1.20 mm, the iodine adsorption value is not less than 900 mg / g, the ash mass fraction is not higher than 3.0%, and the iron mass fraction is not higher than 0.02%, which is conducive to further adsorbing colored substances and low molecular weight organic impurities. The degree of carboxymethyl substitution of carboxymethyl chitosan is 0.65–0.95, and the degree of deacetylation is 80%–95%, which is beneficial for balancing the content of carboxyl and amino coordination sites with aqueous solubility and dispersion performance. The weight-average molecular weight of branched polyethyleneimine is controlled at 10,000–30,000 Da, which is beneficial for balancing amino site density and the ability to enter the pores of D418 type resin. The silica sol has a silica mass fraction of 25%–35% and a silica particle size of 8–25 nm, which is beneficial for the silica sol to be uniformly dispersed in the pore impregnation precursor solution and enter the resin pores. In any embodiment, the weight-average molecular weight of carboxymethyl chitosan is 8000 to 3 × 10⁻⁶. 5 Da.
[0013] In any embodiment, the proportion of wet particles with a particle size of 0.40 to 1.00 mm in the modified resin is not less than 95% of the total mass of the particles, the wet bulk density is 0.72 to 0.88 g / mL, and the sphericity after grinding is not less than 90%.
[0014] Controlling the wet particle size of the modified resin to 0.40–1.00 mm and the wet bulk density to 0.72–0.88 g / mL, with particles within this size range accounting for no less than 95%, helps reduce particle stratification caused by differences in particle size or density during mixing and upward adsorption of the composite adsorbent. Controlling the sphericity after grinding to no less than 90% is beneficial to the mechanical strength and morphological integrity of the resin particles during mixing, column packing, adsorption, and repeated acid-base regeneration, thereby improving the consistency of iron removal performance and the stability of repeated use of the composite adsorbent.
[0015] The second aspect of this application provides a method for preparing a regenerable composite adsorbent for iron removal from amino acid mother liquor, comprising the following steps: soaking modified resin, D418 type resin, and macroporous acrylate-based polar adsorption resin in water for 8–12 hours, and soaking acid-washed coconut shell granular activated carbon for 2–4 hours; after soaking, performing vacuum filtration to remove free water; after filtration, adding the above components to a mixing device and mixing to obtain the regenerable composite adsorbent. Soaking each resin component and acid-washed coconut shell granular activated carbon separately allows the different adsorbent materials to be fully wetted and some gas in the pores to be expelled, which is beneficial for restoring the wet swelling state of each component.
[0016] The third aspect of this application provides a method for removing iron from amino acid mother liquor using the aforementioned renewable adsorbent, comprising the following steps: A1. Adding the renewable composite adsorbent to deionized water to prepare a slurry, and then wet-packing it into an adsorption column; A2. Transporting the amino acid mother liquor to a microfiltration device, and performing circulating microfiltration under conditions of 20–45°C, transmembrane pressure difference of 0.08–0.25 MPa, and membrane surface flow rate of 1.0–3.0 m / s until the mass fraction of suspended solids with a particle size greater than 10 μm in the permeate is no higher than 0.01%, then stopping the microfiltration to obtain a pretreated mother liquor; A3. Adjusting the pH of the pretreated mother liquor to 4.2–5.5 and the temperature to 25–40°C, and then... The bottom of the adsorption column is fed into an adsorption column filled with the regenerable composite adsorbent, and upward adsorption is performed at a flow rate of 2.5-3.0 BV / h; A4. After the liquid starts to flow out from the adsorption column outlet, the initial replacement liquid is collected separately; when the total free amino acid mass concentration in the outlet liquid reaches more than 95% of the total free amino acid mass concentration in the feed mother liquor, the low-iron treatment liquid determination stage begins; the soluble total iron content in the outlet liquid is tested periodically or continuously, and the outlet liquid with a soluble total iron content not higher than 5 mg / L is collected as the low-iron treatment liquid; when the soluble total iron content in the outlet liquid exceeds 5 mg / L for the first time, the feed is stopped, and the outlet liquid corresponding to this test is collected separately from the low-iron treatment liquid.
[0017] Step A1 uses a wet slurry method to fill the regenerable composite adsorbent, which is beneficial for the uniform distribution of different adsorbent materials under wet conditions. Step A2 removes suspended particles, colloids, and some macromolecular impurities from the mother liquor through microfiltration, which helps reduce the risk of adsorption column clogging and adsorption sites being covered by impurities. Step A3 controls the pH of the pretreated mother liquor to 4.2–5.5 and the temperature to 25–40℃, and adopts an upward feeding method of 2.5–3.0 BV / h, which helps to balance the binding capacity between iron ions and iron-organic complexes and the coordination sites of phosphonic acid groups, amino groups, carboxyl groups, and phenolic hydroxyl groups, while also helping to reduce the non-selective adsorption loss of amino acids, so that the treated amino acid mother liquor maintains a high total free amino acid recovery rate. Step A4 uses the soluble total iron content in the effluent not exceeding 5 mg / L as the collection standard for the low-iron treatment liquid, and stops feeding when the soluble total iron content in the effluent first exceeds 5 mg / L, which helps to accurately determine the breakthrough endpoint of the adsorption column.
[0018] In any embodiment, the total soluble iron content of the amino acid mother liquor before treatment is 100–300 mg / L; the filtration accuracy of the microfiltration device is 5–10 μm.
[0019] In any embodiment, in the absence of liquid flow, the regenerable composite adsorbent packed in the adsorption column forms a static bed. The ratio of the height of the static bed of the regenerable composite adsorbent in the adsorption column to the inner diameter of the adsorption column is 3:1 to 8:1, and the height of the free space above the bed is 25% to 45% of the height of the static bed.
[0020] Controlling the ratio of static bed height to adsorption column inner diameter to 3:1 to 8:1, and leaving 25% to 45% free space above the bed, is beneficial for further balancing the contact efficiency between the mother liquor and the adsorbent, bed pressure drop, and upward operation stability.
[0021] In any embodiment, after step A4, the following regeneration steps are further included: A5. While keeping the adsorbent bed in a liquid-immersed state, drain the residual amino acid mother liquor in the adsorption column and replace the residual liquid with 0.5-1.0 BV of deionized water at a flow rate of 1.0-1.5 BV / h; A6. Perform acid washing by passing 3.0 BV of 5.0% hydrochloric acid aqueous solution at a flow rate of 3.0 BV / h from the top of the adsorption column, and let it stand for 20-40 minutes after the acid washing is completed; A7. Pass deionized water at a flow rate of 2.0-3.0 BV / h from the top of the adsorption column, measure the pH of the adsorption column outlet liquid, and stop water washing when the pH of the adsorption column outlet liquid is greater than 4.0; A8. Pass deionized water at a flow rate of 3.0 BV / h from the top of the adsorption column... A9. Administer 3.0 BV of 5.0% sodium hydroxide aqueous solution at a flow rate of V / h for alkaline washing. After administration, allow the solution to stand for 20–40 min. A10. Administer deionized water from the top of the adsorption column at a flow rate of 2.0–3.0 BV / h. Measure the pH and conductivity of the adsorption column outlet solution until the pH of the outlet solution is less than 10.0 and the absolute value of the difference in conductivity between two consecutive 0.5 BV outlet solutions is no greater than 5% of the previous 0.5 BV outlet solution conductivity value. This completes the regeneration of the regenerable composite adsorbent. A11. Administer conditioning water with a pH of 4.2–5.5 from the bottom of the adsorption column at a flow rate of 1.0–1.5 BV / h until the pH of the adsorption column outlet solution is between 4.2 and 5.5. This completes bed conditioning.
[0022] Step A5 involves replacing the residual mother liquor in the bed and pipeline with a small amount of deionized water, which helps reduce material loss and regeneration load caused by direct contact with subsequent acid and alkali solutions. Step A6 involves acid washing with hydrochloric acid solution followed by settling, which allows iron ions adsorbed on coordination sites to dissociate and enter the acid washing solution, thus restoring the iron ion binding sites of the adsorbent. Step A7 involves water washing until the pH of the outlet liquid is greater than 4.0, which helps remove residual hydrochloric acid from the bed. Step A8 involves alkaline washing with sodium hydroxide solution followed by settling, which helps remove residual acidic organic matter and other organic pollutants on the surface and in the pores of the adsorbent, and further restores the pore patency of the adsorbent material. Step A9 uses the relative change in pH and conductivity of the outlet liquid as the basis for determining the water washing endpoint, which helps remove residual alkali and soluble regeneration products. Step A10 involves adjusting the pH of the bed with water to 4.2–5.5, which helps restore the adsorbent to a suitable working state and enables continuous recycling of the regenerable composite adsorbent.
[0023] In any embodiment, the regenerable composite adsorbent is reused for the adsorption treatment in step A3 after completing the regeneration operations in steps A5 to A9 and the bed conditioning in step A10.
[0024] The sequential operation steps A5 to A10 help remove iron ions and residual organic impurities bound to the adsorbent, allowing the bed to return to a pH state suitable for the next adsorption cycle, thereby improving the recycling performance of the composite adsorbent and the economic efficiency of the process.
[0025] In summary, this application has the following beneficial effects: (1) By introducing carboxymethyl chitosan, branched polyethyleneimine, tannic acid and siloxane components into the pores of D418 resin, a modified resin with multiple coordination sites including phosphonic acid, amino, carboxyl and phenolic hydroxyl groups is constructed. This modified resin is then combined with D418 resin, polar adsorption resin in macroporous acrylate system and acid-washed coconut shell granular activated carbon. This combination is beneficial for adsorbing iron ions in different forms in amino acid mother liquor, while effectively adsorbing pigment molecules, thus achieving the dual effect of deep iron removal and decolorization.
[0026] (2) Microfiltration pretreatment, appropriate pH and temperature adjustment and upward fixed bed adsorption can reduce the blockage of suspended impurities and the stratification of adsorbent, which is conducive to enhancing the binding of iron ions and iron-organic complexes with the coordinating groups of adsorbent; while achieving a high iron removal effect, the total free amino acid recovery rate is still maintained at a high level, thus taking into account both the impurity removal effect and the amino acid retention effect of amino acid mother liquor.
[0027] (3) By replacing the residual mother liquor, washing with hydrochloric acid, washing with water, washing with sodium hydroxide, washing again with water and adjusting the pH of the bed, the iron ions and residual organic impurities bound to the adsorbent can be removed, the coordination adsorption sites and pores can be restored, and the regenerated composite adsorbent can be reused for the next cycle of adsorption treatment, thereby extending the service life of the adsorbent and reducing the frequency of material replacement and treatment costs. Detailed Implementation
[0028] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents. The present application will be further described in detail below with reference to embodiments and comparative examples. Example 1
[0029] Preparation of modified resin Weigh the following D418 type resin (matrix is styrene-divinylbenzene crosslinked copolymer, functional group is -NHCH2PO3Na2, wet particle size is 0.315~1.25mm, water content is 57%, wet volume exchange capacity is expressed as Ca) according to dry basis mass fraction. 2+ The following ingredients were used: 100 parts of a mixture with a molecular weight not less than 0.35 mmol / mL, a wet true density of 1.15 g / mL, and a sphericity of not less than 90% after grinding; 8 parts of carboxymethyl chitosan (degree of carboxymethyl substitution 0.80, degree of deacetylation 88%); 3 parts of branched polyethyleneimine (weight average molecular weight 20000 Da); 3 parts of tannic acid; 8 parts of silica sol (silica mass fraction 30%, silica particle size 8–25 nm, based on dry silica); 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane; and 14 parts of ethanol. The specific preparation steps are as follows: S1. By mass, add 3 parts of γ-glycidoxypropyltrimethoxysilane, 14 parts of ethanol and 54 parts of deionized water to a three-necked flask equipped with a stirrer and temperature control. Add 10% acetic acid aqueous solution dropwise to adjust the pH of the system to 4.55. Stir and hydrolyze for 42 min at 32℃ and 400 r / min to obtain silane hydrolysate. S2. Add 8 parts of carboxymethyl chitosan to 135 parts of deionized water and stir at 40℃ and 650r / min for 55min to fully dissolve the carboxymethyl chitosan. Add 3 parts of branched polyethyleneimine and 8 parts of silica sol based on dry silica. Continue stirring for 30min. Then add the silane hydrolysate prepared in step S1. Adjust the pH of the system to 6.4 using a 10% sodium hydroxide aqueous solution to obtain the pore impregnation precursor solution. S3. Add 100 parts of D418 type resin on a dry basis to the pore impregnation precursor solution. Adjust the vacuum degree in the reaction vessel to -0.075MPa at 25°C and maintain it for 32 min. Then restore it to normal pressure and maintain it at normal pressure for 45 min to complete the vacuum impregnation treatment of resin particles. S4. Dissolve 3 parts of tannic acid in 81 parts of deionized water to form an aqueous solution of tannic acid. Add the aqueous solution of tannic acid to the system obtained in step S3. Maintain the system under a vacuum of -0.070 MPa for 22 min, then restore it to atmospheric pressure. Adjust the pH of the system to 8.3 using a 10% sodium hydroxide aqueous solution. Place the pH-adjusted system in a closed reaction vessel and react it at 55℃ and 225 r / min for 6.5 h. S5. After the reaction is complete, the resin particles are filtered out by vacuum filtration using a Buchner funnel lined with 100-mesh alkali-resistant polyester filter cloth. The resin particles are then transferred to a glass washing column with a 100-mesh sieve at the bottom and washed with deionized water at a flow rate of 3 BV / h. The pH and absorbance at 280 nm of the washing solution are measured. The washing solution is washed until the pH is 7.0 and the absorbance at 280 nm is no greater than 0.05. The washed resin particles are then vacuum dried at 45°C and a vacuum degree of -0.070 MPa until the water content of the resin particles is 51%, thus obtaining the modified resin.
[0030] The wet particle size of the obtained modified resin is mainly distributed in the range of 0.40 to 1.00 mm, the wet bulk density is 0.80 g / mL, the particles with a particle size of 0.40 to 1.00 mm account for 97% of the total particle mass, and the sphericity after grinding is 93%.
[0031] 2. Preparation of Renewable Composite Adsorbents Modified resin, D418 type resin, macroporous acrylate polar adsorption resin, and acid-washed coconut shell granular activated carbon were placed in separate wide-mouthed glass bottles with lids. Deionized water was added to each bottle, ensuring the water level was 20 mm above the surface of the corresponding resin particles. The first three resins were soaked at 25±2℃ for 10 hours, while the acid-washed coconut shell granular activated carbon was soaked at 25±2℃ for 3 hours. After soaking, each wet material was filtered under reduced pressure using a Buchner funnel lined with 100-mesh water-resistant polyester filter cloth to remove the soaking liquid. After filtration, the material was left to drain on the filter cloth for 15 minutes until no continuous water droplets flowed from the surface. Samples were taken to determine the moisture content of each wet component, and the target dry basis mass was converted to wet weight based on the moisture content.
[0032] Weigh out the following components by dry weight: 81 parts modified resin, 11 parts D418 type resin, 6 parts macroporous acrylate polar adsorption resin, and 2 parts acid-washed coconut shell granular activated carbon. Add each component to a low-speed mixer with adjustable speed and mix at 15 r / min for 22 min to ensure uniform dispersion of the different components, thus obtaining a regenerable composite adsorbent.
[0033] The macroporous acrylate-based polar adsorption resin has a wet particle size of 0.40–1.00 mm, a specific surface area of 480 m² / g, and an average pore size of 15 nm; the acid-washed coconut shell granular activated carbon has a particle size of 0.45–1.20 mm, an iodine adsorption value of 950 mg / g, an ash content of 2.0%, and an iron content of 0.01%.
[0034] 3. Adsorption iron removal and regeneration treatment of amino acid mother liquor A1. Add 1.5 times the total volume of deionized water to the obtained renewable composite adsorbent to ensure uniform suspension of the wet adsorbent under slow stirring, resulting in a fluid adsorbent slurry. Before loading the column, add deionized water to the adsorption column to achieve an initial water level of 35% of the predetermined bed height. Slowly stir the adsorbent slurry at 5–10 r / min to ensure uniform dispersion of different materials. Continuously add the adsorbent slurry from the top of the adsorption column at a rate of 0.5 BV / h. During loading, maintain the liquid level in the adsorption column at least 75 mm above the formed bed surface to prevent air from entering the bed and to avoid excessively rapid loading that could cause significant stratification. After the adsorbent slurry is added, allow it to settle for 30 minutes to obtain an adsorption column filled with the renewable composite adsorbent. The column has an inner diameter of 50 mm, a static wet bed height of 250 mm, a bed height to inner diameter ratio of 5:1, and a free space height above the bed of 35% of the bed height.
[0035] A2. Take a glutamic acid mother liquor with a total free amino acid mass fraction of 20% and a total soluble iron content of 200 mg / L. Transfer the glutamic acid mother liquor to a ceramic membrane microfiltration device with a filtration accuracy of 5 μm. Adjust the temperature of the glutamic acid mother liquor to 30℃, control the transmembrane pressure difference to 0.15 MPa and the membrane surface flow rate to 2.0 m / s, and perform circulating microfiltration. Collect the permeate. When the mass fraction of suspended solids with a particle size greater than 10 μm in the obtained permeate is not higher than 0.01%, stop microfiltration to obtain the pretreated mother liquor.
[0036] A3. Adjust the pH of the pretreatment mother liquor to 4.8 and the temperature to 32℃ using a 10.0% sodium hydroxide aqueous solution to obtain the mother liquor to be adsorbed. After purging the bed gas by introducing 1.8 BV of deionized water from the bottom at a flow rate of 1.2 BV / h, introduce the mother liquor to be adsorbed from the bottom of the adsorption column and perform upward adsorption treatment at a flow rate of 2.8 BV / h.
[0037] A4. After the liquid begins to exit from the adsorption column, the initial replacement liquid is collected separately. When the total free amino acid concentration in the outlet liquid reaches more than 95% of the total free amino acid concentration in the feed mother liquor, samples are taken every 30 minutes to detect the soluble total iron content in the outlet liquid. The outlet liquid with a soluble total iron content not exceeding 5 mg / L is collected as the low-iron treatment liquid. When the soluble total iron content in the outlet liquid exceeds 5 mg / L for the first time, the feed is stopped, and the corresponding outlet liquid and the low-iron treatment liquid are collected separately. A5. After stopping the feeding of glutamic acid mother liquor into the adsorption column, close the feed valve, drain the residual glutamic acid mother liquor in the adsorption column, and introduce 0.8 BV of deionized water from the top of the adsorption column at a flow rate of 1.2 BV / h to replace the residual mother liquor in the bed and pipeline. During the drainage and deionized water replacement process, keep the adsorbent bed in a liquid-immersed state at all times.
[0038] A6. Acid washing is performed by passing 3.0 BV of 5.0% hydrochloric acid aqueous solution through the top of the adsorption column at a flow rate of 3.0 BV / h. After the flow is completed, the column is allowed to stand for 30 min.
[0039] A7. Wash the adsorption column with deionized water at a flow rate of 2.5 BV / h from the top until the pH of the outlet liquid is greater than 4.0.
[0040] A8. A 3.0 BV, 5.0% sodium hydroxide aqueous solution was passed through the top of the adsorption column at a flow rate of 3.0 BV / h for alkaline washing. After the passage was completed, the column was allowed to stand for 30 min.
[0041] A9. Deionized water is introduced from the top of the adsorption column at a flow rate of 2.5 BV / h. The pH and conductivity of the outlet liquid are measured every 0.5 BV introduced until the pH of the outlet liquid is less than 10.0 and the absolute value of the difference in conductivity between two consecutive 0.5 BV outlet liquids is not greater than 5% of the conductivity value of the previous 0.5 BV outlet liquid. Regeneration is then complete.
[0042] A10. Introduce pH 5.0 conditioning water from the bottom of the adsorption column at a flow rate of 1.2 BV / h until the pH of the outlet liquid of the adsorption column stabilizes at 5.0, thus completing the bed conditioning. The regenerable composite adsorbent can be reused for adsorption in step A3.
[0043] The total free amino acid mass fraction in the pretreated mother liquor was 20%, the total soluble iron content was 200 mg / L, and the total free amino acid recovery rate was 99.3%. Example 2
[0044] Referring to the preparation method of the modified resin in Example 1, 8 parts of carboxymethyl chitosan were replaced with 10 parts of carboxymethyl chitosan, 3 parts of branched polyethyleneimine were replaced with 4 parts of branched polyethyleneimine, 3 parts of tannic acid were replaced with 4 parts of tannic acid, 8 parts of silica sol (based on dry silica) were replaced with 10 parts of silica sol (based on dry silica), 3 parts of γ-glycidoxypropyltrimethoxysilane were replaced with 4 parts of γ-glycidoxypropyltrimethoxysilane, 14 parts of ethanol were replaced with 18 parts of ethanol, and 270 parts of deionized water were replaced with 320 parts of deionized water.
[0045] Replace 54 parts of deionized water in step S1 with 48 parts of deionized water, change the pH of the mixture from 4.55 to 4.3, change the hydrolysis temperature from 32℃ to 28℃, change the stirring speed from 400 r / min to 300 r / min, and change the stirring and hydrolysis time from 42 min to 35 min; replace 135 parts of deionized water in step S2 with 160 parts of deionized water, change the carboxymethyl chitosan dissolution temperature from 40℃ to 35℃, change the stirring speed from 650 r / min to 500 r / min, change the carboxymethyl chitosan dissolution time from 55 min to 40 min, change the continued stirring time after adding branched polyethyleneimine and silica sol from 30 min to 20 min, and change the system pH from 6.4 to 6.0. Replace the immersion temperature in step S3 from 25℃ to 20℃, the vacuum degree from -0.075MPa to -0.085MPa, the vacuum holding time from 32min to 25min, and the holding time after restoring atmospheric pressure from 45min to 30min; replace 81 parts of deionized water in step S4 with 112 parts of deionized water, the vacuum degree from -0.070MPa to -0.080MPa, the vacuum holding time from 22min to 15min, and adjust the system pH... The following steps were performed: 8.3 was replaced with 8.0; the reaction temperature was replaced with 52℃; the stirring speed was replaced with 150 r / min; the reaction time was replaced with 5h; the washing flow rate in step S5 was replaced with 2BV / h; the vacuum drying temperature was replaced with 40℃; the vacuum degree was replaced with -0.070MPa; and the moisture content at the drying endpoint was replaced with 58% instead of 51%. All other steps remained the same as in Example 1, resulting in the modified resin.
[0046] The wet particle size of the obtained modified resin is mainly distributed in the range of 0.40 to 1.00 mm, the wet bulk density is 0.82 g / mL, the particles with a particle size of 0.40 to 1.00 mm account for 98% of the total particle mass, and the sphericity after grinding is 94%.
[0047] Referring to the preparation method of the renewable composite adsorbent in Example 1, 81 parts of modified resin were replaced with 86 parts of modified resin, 11 parts of D418 type resin were replaced with 8 parts of D418 type resin, 6 parts of macroporous acrylate polar adsorbent were replaced with 4 parts of macroporous acrylate polar adsorbent, and the amount of acid-washed coconut shell granular activated carbon was kept at 2 parts. Other aspects remained the same as in Example 1, thus obtaining the renewable composite adsorbent.
[0048] The adsorption and regeneration methods for the obtained regenerable composite adsorbent are the same as those in Example 1.
[0049] In Example 2, the total free amino acid recovery rate was 99.6%. Example 3
[0050] Referring to the preparation method of the modified resin in Example 1, 8 parts of carboxymethyl chitosan were replaced with 6 parts of carboxymethyl chitosan, 3 parts of branched polyethyleneimine were replaced with 2 parts of branched polyethyleneimine, 3 parts of tannic acid were replaced with 2 parts of tannic acid, 8 parts of silica sol (based on dry silica) were replaced with 6 parts of silica sol (based on dry silica), 3 parts of γ-glycidoxypropyltrimethoxysilane were replaced with 2 parts of γ-glycidoxypropyltrimethoxysilane, 14 parts of ethanol were replaced with 10 parts of ethanol, and 270 parts of deionized water were replaced with 220 parts of deionized water.
[0051] Replace 54 parts of deionized water in step S1 with 55 parts of deionized water, change the pH of the mixture from 4.55 to 4.8, change the hydrolysis temperature from 32℃ to 35℃, change the stirring speed from 400 r / min to 500 r / min, and change the stirring and hydrolysis time from 42 min to 50 min; replace 135 parts of deionized water in step S2 with 110 parts of deionized water, change the carboxymethyl chitosan dissolution temperature from 40℃ to 45℃, change the stirring speed from 650 r / min to 800 r / min, change the carboxymethyl chitosan dissolution time from 55 min to 70 min, change the continued stirring time after adding branched polyethyleneimine and silica sol from 30 min to 40 min, and change the system pH from 6.4 to 6.8. In step S3, the immersion temperature is changed from 25℃ to 30℃, the vacuum degree is changed from -0.075MPa to -0.065MPa, the vacuum holding time is changed from 32min to 40min, and the holding time after restoring atmospheric pressure is changed from 45min to 60min; in step S4, 81 parts of deionized water are changed to 55 parts of deionized water, the vacuum degree is changed from -0.070MPa to -0.060MPa, the vacuum holding time is changed from 22min to 30min, and the system pH is changed from... 8.3 was replaced with 8.6, the reaction temperature was replaced with 58℃, the stirring speed was replaced with 300 r / min, and the reaction time was replaced with 8h. The washing flow rate in step S5 was replaced with 4BV / h, the vacuum drying temperature was replaced with 50℃, the vacuum degree was replaced with -0.070MPa, and the moisture content at the drying endpoint was replaced with 45%. All other conditions remained the same as in Example 1, and the modified resin was obtained.
[0052] The wet particle size of the obtained modified resin is mainly distributed in the range of 0.40 to 1.00 mm, the wet bulk density is 0.78 g / mL, the particles with a particle size of 0.40 to 1.00 mm account for 96% of the total particle mass, and the sphericity after grinding is 91%.
[0053] Referring to the preparation method of the renewable composite adsorbent in Example 1, 81 parts of modified resin were replaced with 74 parts of modified resin, 11 parts of D418 type resin were replaced with 14 parts of D418 type resin, 6 parts of macroporous acrylate polar adsorbent were replaced with 8 parts of macroporous acrylate polar adsorbent, and the amount of acid-washed coconut shell granular activated carbon was kept at 4 parts. Other aspects remained the same as in Example 1, thus obtaining the renewable composite adsorbent.
[0054] The adsorption and regeneration methods for the obtained regenerable composite adsorbent are the same as those in Example 1.
[0055] In Example 3, the total free amino acid recovery rate was 99.1%.
[0056] Comparative Example 1 The preparation methods of Comparative Example 1 and Example 1 are basically the same, except that in the preparation process of the renewable composite adsorbent, 81 parts of modified resin are replaced with 81 parts of D418 type resin, and the wet water content of the D418 type resin is 57%. The rest is the same as that of Example 1.
[0057] Comparative Example 2 The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that in the preparation process of the renewable composite adsorbent, 11 parts of D418 type resin, 6 parts of macroporous acrylate polar adsorption resin and 2 parts of acid-washed coconut shell granular activated carbon are replaced with 19 parts of modified resin, and the rest is the same as that of Example 1.
[0058] Comparative Example 3 The preparation method of Comparative Example 3 is basically the same as that of Example 1, except that in step S2, 3 parts of branched polyethyleneimine are not added, while the rest is the same as that of Example 1.
[0059] Comparative Example 4 The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that in step S4, 3 parts of tannic acid are not added, while the rest is the same as that of Example 1.
[0060] Comparative Example 5 The preparation method of Comparative Example 5 is basically the same as that of Example 1, except that in step S2, 8 parts of silica sol based on dry silica are not added, and 18.67 parts of deionized water are added. Otherwise, it is the same as Example 1.
[0061] Comparative Example 6 The preparation method of Comparative Example 6 is basically the same as that of Example 1, except that in step S2, 8 parts of carboxymethyl chitosan are not added, while the rest is the same as that of Example 1.
[0062] Comparative Example 7 The preparation method of Comparative Example 7 is basically the same as that of Example 1, except that step S3 is adjusted to be carried out under normal pressure. That is, 100 parts of D418 type resin are added to the pore impregnation precursor solution, stirred for 32 minutes at 25°C and normal pressure, and then kept under normal pressure for 45 minutes. The rest is the same as that of Example 1.
[0063] Comparative Example 8 The preparation method of Comparative Example 8 is basically the same as that of Example 1, except that in step S1, 3 parts of γ-glycidoxypropyltrimethoxysilane are not added, while the rest is the same as that of Example 1.
[0064] Comparative Example 9 The preparation method of Comparative Example 9 is basically the same as that of Example 1, except that the pH of the mixture in step S1 is adjusted from 4.55 to 3.5, while the rest is the same as that of Example 1.
[0065] Comparative Example 10 The preparation method of Comparative Example 10 is basically the same as that of Example 1, except that in step S2, 8 parts of carboxymethyl chitosan are added to 135 parts of deionized water and stirred at 40°C and 650 r / min for 55 min to fully dissolve the carboxymethyl chitosan. Then, 3 parts of branched polyethyleneimine, 8 parts of silica sol (based on dry silica) and 3 parts of tannic acid are added and stirred for another 30 min. Subsequently, the silane hydrolysate prepared in step S1 is added, and the pH of the system is adjusted to 6.4 using a 10% sodium hydroxide aqueous solution to obtain the pore impregnation precursor solution. In step S4, tannic acid is not added. 81 parts of deionized water are added to the system obtained in step S3 and kept under a vacuum of -0.070 MPa for 22 min. The system is then restored to atmospheric pressure, and the pH of the system is adjusted to 8.3 using a 10% sodium hydroxide aqueous solution. The pH-adjusted system is placed in a closed reaction vessel and reacted at 55°C and 225 r / min for 6.5 h. Everything else remains the same as in Example 1.
[0066] Comparative Example 11 S1. By weight, add 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 14 parts of ethanol, and 54 parts of deionized water to a three-necked flask equipped with a stirrer and temperature control. Adjust the pH of the system to 4.55 by adding a 10% (w / w) aqueous acetic acid solution dropwise. Stir and hydrolyze for 42 min at 32℃ and 400 rpm to obtain a silane hydrolysate. S2. Add 8 parts of carboxymethyl chitosan to 216 parts of deionized water. Stir for 55 min at 40℃ and 650 rpm to fully dissolve the carboxymethyl chitosan. Add 3 parts of branched... Polyethyleneimine and 8 parts of silica sol (based on dry silica) were stirred for 30 min. Then, the silane hydrolysate prepared in step S1, 100 parts of D418 resin (based on dry basis), and 3 parts of tannic acid were added. The pH of the system was adjusted to 8.3 using a 10% sodium hydroxide aqueous solution. The pH-adjusted system was placed in a sealed reaction vessel and reacted at 55℃ and 225 r / min for 6.5 h. After the reaction (S3), the mixture was filtered under reduced pressure using a Buchner funnel lined with 100-mesh alkali-resistant polyester filter cloth. The resulting filter cake was a gel-like aggregate. The aggregate was transferred to a washing column and washed at a flow rate of 3 BV / h until the relative difference in absorbance between two consecutive samples was no greater than 5%. The washed aggregate was then vacuum dried at 45℃ and a vacuum degree of -0.070 MPa until the moisture content was 51%, yielding the control resin material of Comparative Example 11.
[0067] In the preparation of the renewable composite adsorbent, 81 parts of modified resin were replaced with 81 parts of control resin material, and everything else remained the same as in Example 1.
[0068] The renewable composite adsorbents prepared in Examples 1-3 and Comparative Examples 1-11 were tested using adsorption columns of the same specifications, and the same batch of glutamic acid mother liquor was used as the treatment liquid. Three independent parallel adsorption experiments were set up for each sample. The results in the table are the average values of the three experiments.
[0069] 1. Determination of soluble total iron removal performance During the adsorption process, when the total free amino acid content in the adsorption column outlet liquid reaches more than 95% of the total free amino acid content in the feed mother liquor, the outlet liquid is collected in segments with a collection unit of 30 minutes each, and the total soluble iron content in the outlet liquid of each collection unit is measured.
[0070] The pretreatment mother liquor before adsorption and the effluent collected from each segment were filtered through a 0.45 μm aqueous filter membrane and used as the test samples. For the pretreatment mother liquor before adsorption, 1.00 mL of sample was accurately transferred; for the adsorption column effluent, 5.00 mL of sample was accurately transferred and added to 5.00 mL of analytical grade nitric acid and 1.00 mL of 30% hydrogen peroxide aqueous solution for microwave digestion. After digestion, the solution was cooled to room temperature and quantitatively transferred to a 50.00 mL volumetric flask, and diluted to the mark with a diluent with the same acid matrix as the standard solution. The final nitric acid concentration of the standard solution, calibration blank, and test solution was kept consistent; the calibration blank contained the same acid matrix as the standard solution.
[0071] Iron content in the samples was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES) at a wavelength of 238.204 nm. A series of standard solutions with concentrations of 0.10 mg / L, 0.50 mg / L, 1.00 mg / L, 2.00 mg / L, 5.00 mg / L, and 10.00 mg / L were prepared using an iron standard stock solution. A standard curve was plotted with iron concentration on the x-axis and emission intensity on the y-axis, with a correlation coefficient (R²) of no less than 0.999. Each sample was measured in triplicate, and the spiked recoveries ranged from 90% to 110%. To compare the iron removal depth of different adsorbents under the same cumulative throughput, effluent samples were collected separately when the cumulative throughput reached 20.0 BV. The total soluble iron content in the effluent at 20 BV was determined, and the iron removal rate at 20 BV was calculated using the following formula: Soluble total iron removal rate (%) at 20 BV = (Soluble total iron content in pretreatment mother liquor - Soluble total iron content in effluent after cumulative treatment of 20.0 BV) / Soluble total iron content in pretreatment mother liquor × 100% In the above performance comparison test, in order to determine the soluble total iron content of the outlet liquid at 20.0 BV, the pretreatment mother liquor was introduced until the cumulative treatment volume reached 20.0 BV; during actual production operation, the feed was stopped or the adsorption column was switched when the soluble total iron content of the outlet liquid first exceeded 5 mg / L.
[0072] When the iron content at the outlet of the preceding collection unit is no higher than 5 mg / L and the iron content at the outlet of the following collection unit is greater than 5 mg / L, the effective single-column throughput is calculated according to the following formula: Effective single-column throughput (BV) = V × t - BV0 In the formula, V is the actual upward adsorption flow rate in step A3; t is the time from the start of feeding to the first time the total soluble iron in the outlet liquid exceeds 5 mg / L; BV0 is the bed volume multiple calculated from the volume of the front-stage replacement liquid; the effective single-column throughput refers to the ratio of the qualified feed liquid volume to the bed volume, which is measured from the point when the total free amino acid concentration in the outlet liquid reaches more than 95% of the feed mother liquor. The front-stage replacement liquid is collected separately and is not included in this indicator.
[0073] 2. Determination of total free amino acid recovery rate Take the pretreatment mother liquor before adsorption treatment and the collection units of each qualified low-iron treatment solution, mix them thoroughly, and then take 1.00 mL of the sample. Dilute the sample stepwise with 0.02 mol / L hydrochloric acid aqueous solution to ensure that the concentration of each amino acid in the sample is within the linear detection range of the instrument. Centrifuge the diluted solution at 10000×g for 10 min, and filter the supernatant through a 0.22 μm aqueous filter membrane as the test solution.
[0074] The content of each free amino acid in the sample was determined using an automated amino acid analyzer. Separation was performed using a cation exchange column with gradient elution using sodium citrate buffer, followed by ninhydrin post-column derivatization for detection. The detection wavelength for most amino acids was 570 nm, while that for proline and hydroxyproline was 440 nm. External standard calibration was performed using a mixed amino acid standard solution corresponding to the major amino acids in the sample. Qualitative analysis was based on retention time, and quantification was based on peak area. The total free amino acid concentration was obtained by summing the mass concentrations of each free amino acid in the sample. The correlation coefficient R² of the standard curve was not less than 0.999, and the spiked recovery rate was 90%–110%.
[0075] Record the volume of pretreatment mother liquor entering the adsorption column during the low-iron treatment liquid collection stage, as well as the volume of each qualified low-iron treatment liquid collection unit. The total free amino acid recovery rate is calculated according to the following formula: Total free amino acid recovery rate (%) = [Σ(C i ×V i ] ÷ (C0 × V0) × 100% In the formula, C i V represents the total free amino acid concentration in the i-th qualified low-iron treatment solution collection unit; i C0 represents the volume of the i-th qualified low-iron treatment solution collection unit; C0 represents the total free amino acid mass concentration in the pretreatment mother liquor; V0 represents the volume of the pretreatment mother liquor from the starting point of low-iron treatment solution collection to the point where the soluble total iron content first exceeds 5 mg / L. The upstream replacement solution and the collection units where the outlet iron content first exceeds 5 mg / L are not included in the qualified low-iron treatment solution count.
[0076] 3. Measurement of absorbance Absorbance was measured using a UV-Vis spectrophotometer, with deionized water as a blank, and a quartz cuvette with a path length of 1 cm. For the washing solution in step S5 of the modified resin preparation, the absorbance was measured directly at 280 nm, with an absorbance of no more than 0.05 at 280 nm used as one of the endpoint criteria. For the effluent after adsorption treatment, the effluent after a cumulative treatment of 20.0 BV was collected, allowed to stand at 25±2℃ for 10 min, centrifuged at 5000×g for 10 min, and the supernatant was filtered through a 0.45 μm aqueous filter membrane. Depending on the sample color intensity, the sample was diluted with deionized water to ensure the measured absorbance at 400 nm was within the range of 0.10–1.00. Each sample was measured in triplicate. The measured absorbance was corrected according to the sample dilution factor. A 400,校正 =A 400,实测 ×Sample dilution factor D The samples before and after adsorption treatment were processed using the same type of cuvette and under the same centrifugation, filtration, and temperature conditions. The absorbance of the effluent at 400 nm listed in the table is the absorbance of the effluent after dilution correction following a cumulative treatment of 20.0 BV. The results are the average of the three sets of experiments.
[0077] 4. Determination of regeneration performance The prepared regenerable composite adsorbent was subjected to three independent parallel experiments under the common adsorption test conditions described above. The results in the table are the average values of the three experiments. Five consecutive adsorption-regeneration cycles were performed, with each cycle conducted under the conditions of Example 1. The same batch of glutamic acid mother liquor was used in each adsorption cycle. The soluble total iron content in the effluent was determined after a cumulative treatment of 20.0 BV, and the iron removal rate at 20 BV was calculated. Feeding continued until the soluble total iron content in the effluent first exceeded 5 mg / L, and the effective single-column throughput was calculated. The retention rate of soluble total iron removal performance and the retention rate of treatment capacity at 20 BV in the nth cycle were calculated using the following formulas: The retention rate of soluble total iron removal performance at 20 BV in the nth cycle (%) = Iron removal rate in the nth cycle at a cumulative treatment of 20.0 BV ÷ Iron removal rate in the first cycle at a cumulative treatment of 20.0 BV × 100% The processing capacity retention rate (%) of the nth cycle = the effective single-column processing capacity of the nth cycle ÷ the effective single-column processing capacity of the 1st cycle × 100%.
[0078] The renewable adsorbents prepared in Examples 1-3 and Comparative Examples 1-11 were tested, and the test results are shown in Table 1.
[0079] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-11 Example 1 2.1 99.0 0.32 28.0 Example 2 1.8 99.1 0.28 30.8 Example 3 3.2 98.4 0.41 25.2 Comparative Example 1 8.5 95.8 0.85 15.4 Comparative Example 2 5.2 97.4 0.68 19.6 Comparative Example 3 4.9 97.6 0.52 21.0 Comparative Example 4 4.8 97.6 0.61 21.5 Comparative Example 5 4.3 97.9 0.55 22.4 Comparative Example 6 6.2 96.9 0.48 17.3 Comparative Example 7 5.1 97.5 0.58 19.6 Comparative Example 8 7.8 96.1 0.72 15.9 Comparative Example 9 5.6 97.2 0.63 18.2 Comparative Example 10 7.0 96.5 0.69 16.4 Comparative Example 11 12.0 94.0 0.89 11.7 Table 2 Results of continuous adsorption-regeneration performance test in Example 1 1st time 2.1 99.0 100.0 28.0 100.0 2nd time 2.3 98.9 99.9 27.1 96.8 3rd 2.5 98.8 99.8 26.1 93.2 4th 2.8 98.6 99.6 25.2 90.0 5th 3.0 98.5 99.5 23.8 85.0 Table 3. Results of the 5th cycle performance test for different adsorbents Example 1 85.0 Example 2 88.0 Example 3 82.1 Comparative Example 1 81.8 Comparative Example 5 65.2 Comparative Example 8 54.7 Based on Tables 1, 2, and 3 above, a comparison of the results of Examples 1-3 and Comparative Examples 1-11 of this application shows that, in the preparation of modified resins and regenerable composite adsorbents, compared to Comparative Example 1 which replaced the modified resin with D418 type resin, Comparative Example 2 which replaced D418 type resin, macroporous acrylate polar adsorption resin, and acid-washed coconut shell granular activated carbon with modified resin, Comparative Example 3 which did not add branched polyethyleneimine, Comparative Example 4 which did not add tannic acid, Comparative Example 5 which did not add silica sol, Comparative Example 6 which did not add carboxymethyl chitosan, Comparative Example 7 which replaced vacuum impregnation with atmospheric pressure impregnation, Comparative Example 8 which did not add γ-glycidyl etheroxypropyltrimethoxysilane, Comparative Example 9 which adjusted the silane hydrolysis pH from 4.55 to 3.5, Comparative Example 10 which added tannic acid to the pore impregnation precursor solution in step S2 in advance, and Comparative Example 11 which replaced the control resin material. Examples 1-3 utilize a vacuum impregnation process, which facilitates the full entry of the modified precursor liquid into the resin's interconnecting channels. This allows for the in-situ composite formation of carboxymethyl chitosan, branched polyethyleneimine, tannic acid, and a silica sol / silane coupling agent system within the interconnecting channels of the D418 resin. This process increases the number of amino, carboxyl, and phenolic hydroxyl sites that can participate in iron binding, enhancing the resin's coordination adsorption capacity for soluble total iron, reducing the iron ion content in the amino acid mother liquor, improving solution color, and simultaneously exhibiting good regeneration and reuse performance.
[0080] Comparative Example 1 uses D418 type resin instead of modified resin. It lacks multi-coordination sites such as amino, carboxyl and phenolic hydroxyl groups constructed in situ in the pores, resulting in insufficient coordination adsorption capacity for soluble total iron in amino acid mother liquor, which is not conducive to effective iron removal and improvement of solution color.
[0081] Comparative Example 2 did not include D418 type resin, macroporous acrylate polar adsorption resin, or acid-washed coconut shell granular activated carbon. This resulted in the absence of the rapid chelation of iron ions by D418 type resin and the deep decolorization function of macroporous acrylate polar adsorption resin and activated carbon for organic pigments and iron-organic complexes. Consequently, the organic load was high and the adsorption capacity was limited, which was not conducive to the effective removal of iron and the improvement of solution color.
[0082] Comparative Example 3 did not add branched polyethyleneimine, which reduced the number of primary and secondary amino coordination sites provided by branched polyethyleneimine in the modified resin, decreased the amino density of the intrapore network, reduced the adsorption capacity for iron ions and iron ion complexes, and increased the solution color.
[0083] Comparative Example 4 did not add tannic acid, which resulted in the modified resin lacking the phenolic hydroxyl coordination sites provided by tannic acid. This reduced the resin's ability to capture iron-peptides and iron-pigment complexes, thus decreasing the composite adsorbent's continuous iron removal capacity and color improvement effect.
[0084] Comparative Example 5 did not include silica sol. The lack of silica sol to form a silicon-oxygen inorganic network with silane resulted in an uneven distribution of the cross-linked network structure within the pores, which was not conducive to the full contact between the coordinating groups and iron ions and iron ion complexes. Consequently, the iron removal capacity decreased, and the regeneration performance was poor.
[0085] Comparative Example 6, which did not contain carboxymethyl chitosan, lacked the large number of carboxyl and amino coordination sites provided by carboxymethyl chitosan, resulting in a decreased adsorption capacity for iron ions and a reduced iron removal performance.
[0086] Comparative Example 7 replaced the vacuum impregnation treatment in step S3 with atmospheric pressure stirring treatment, which is not conducive to the full entry of the impregnation precursor solution into the internal interconnecting channels of the D418 resin, and is not conducive to the full contact between the coordinating groups and iron ions and iron ion complexes, resulting in a decrease in iron removal performance. Comparative Example 8 did not add 3 parts of γ-glycidoxypropyltrimethoxysilane, which is not conducive to the composite modification treatment between silica sol, carboxymethyl chitosan, branched polyethyleneimine and D418 resin. The iron removal performance and decolorization performance of the resulting modified resin were reduced, and the regeneration performance was poor.
[0087] In Comparative Example 9, the pH in the silane hydrolysis step was adjusted from 4.55 to 3.5, which caused the silane hydrolysis to form monosilanols, short-chain siloxane oligomers, and epoxy groups to prematurely open the ring and lose some of their reactivity. This was not conducive to the formation of a large-span network structure with silica sol, carboxymethyl chitosan, branched polyethyleneimine, and tannic acid, resulting in an increase in the total soluble iron content at the outlet and a decrease in the iron removal rate.
[0088] In Comparative Example 10, tannic acid was added to the pore impregnation precursor solution in step S2 in advance. This caused the tannic acid and branched polyethyleneimine and other components to easily electrostatically combine and form insoluble flocculent precipitates before entering the pores of the D418 resin. As a result, some modified components could not fully enter the resin to connect the pores, which was not conducive to the formation of a relatively uniform composite network structure in the pores. Consequently, the iron removal performance, decolorization performance and effective single-column treatment capacity of the modified resin were reduced.
[0089] Comparative Example 11 did not undergo vacuum impregnation and atmospheric pressure maintenance steps. As a result, carboxymethyl chitosan, branched polyethyleneimine, tannic acid, silica sol, and silane could not form a stable composite structure in the internal pores of the D418 resin. This was not conducive to the modified components exerting their adsorption capacity for iron ions of different valence states and iron ion complexes. It also affected the iron removal capacity of the D418 resin, resulting in a significant reduction in the iron removal performance, decolorization performance, and effective single-column treatment capacity of the obtained control resin.
[0090] As can be seen from Examples 1-3, the regenerable composite adsorbent prepared under suitable raw material composition and process conditions has a stable and high removal capacity for soluble total iron, and can effectively improve the color of the effluent and maintain a low A content. 400 level.
[0091] As shown in Table 2, after five adsorption-regeneration cycles, the iron removal rate and single-column throughput of Example 1 remained at a high level, indicating that the composite adsorbent has good regeneration and reuse performance.
[0092] As shown in Table 3, after five adsorption-regeneration cycles, the treatment capacity retention rate of Examples 1-3 remained at a high level. In contrast, the treatment capacity retention rate of Comparative Example 1 did not decrease significantly, indicating that the D418 resin itself has a certain degree of acid-base regeneration stability. However, as shown in Table 1, the initial effective single-column treatment capacity of Comparative Example 1 was low, and its iron removal capacity was poor. The iron removal capacity of Comparative Example 5 (without silica sol) and Comparative Example 8 (without silane) both showed significant decline. This indicates that silica sol and silane are beneficial to improving the cycle stability of the intrapore composite network, thereby enhancing the continuous treatment capacity of the modified resin under repeated acid-base regeneration conditions, giving it better regeneration and reuse performance.
[0093] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A regenerable composite adsorbent for iron removal from amino acid mother liquor, characterized in that, The renewable composite adsorbent is composed of 74-86 parts of modified resin, 8-14 parts of D418 type resin, 4-8 parts of macroporous acrylate polar adsorption resin, and 2-4 parts of acid-washed coconut shell granular activated carbon, based on dry basis mass, and the sum of the dry basis mass of each component is 100 parts. The method for preparing the modified resin includes the following steps: S1. Mix γ-glycidoxypropyltrimethoxysilane, ethanol and water, adjust the pH to 4.3-4.8, and hydrolyze under stirring to obtain silane hydrolysate; S2. Dissolve carboxymethyl chitosan in water, add branched polyethyleneimine and silica sol, stir, add silane hydrolysate, and adjust the pH to 6.0-6.8 to obtain the pore impregnation precursor solution. S3. Add D418 type resin to the pore impregnation precursor solution and maintain it at -0.085 to -0.065 MPa for 25 to 40 minutes, then restore it to normal pressure and maintain it at normal pressure for 30 to 60 minutes. S4. Disperse tannic acid in water to obtain an aqueous solution of tannic acid. Add the aqueous solution of tannic acid to the system obtained in step S3. Maintain the pressure at -0.080 to -0.060 MPa for 15 to 30 minutes, restore to normal pressure, adjust the pH to 8.0 to 8.6, and place it in a closed reaction vessel. React at 52 to 58°C for 5 to 8 hours. S5. After the reaction is complete, the resin particles are obtained by vacuum filtration under reduced pressure, washed with water and vacuum dried to a water content of 45% to 58%, thus obtaining the modified resin.
2. The regenerable composite adsorbent for iron removal from amino acid mother liquor according to claim 1, characterized in that, The preparation of the modified resin includes the following steps: S1. Mix 2-4 parts of γ-glycidoxypropyltrimethoxysilane, 10-18 parts of ethanol and 15%-25% of the total amount of added deionized water, adjust the pH of the mixture to 4.3-4.8 using an acetic acid aqueous solution with a mass fraction of 8-12%, and stir and hydrolyze for 35-50 minutes at 28-35℃ and 300-500 r / min to obtain silane hydrolysate; S2. Add 6-10 parts of carboxymethyl chitosan to 45%-55% of the total amount of added deionized water, stir at 35-45℃ and 500-800 r / min for 40-70 min, add 2-4 parts of branched polyethyleneimine and 6-10 parts of silica sol based on dry silica, continue stirring for 20-40 min, then add the silane hydrolysate prepared in step S1, and adjust the pH of the system to 6.0-6.8 using an 8-12% sodium hydroxide aqueous solution to obtain the pore impregnation precursor solution; S3. Add 100 parts of D418 type resin on a dry basis to the pore impregnation precursor solution. Adjust the vacuum degree in the reaction vessel to -0.085 to -0.065 MPa at 20 to 30°C and maintain it for 25 to 40 minutes. Then restore it to atmospheric pressure and maintain it at atmospheric pressure for 30 to 60 minutes. S4. Dissolve 2-4 parts of tannic acid in the remaining deionized water to form an aqueous tannic acid solution. Add the aqueous tannic acid solution to the system obtained in step S3. Maintain the system under a vacuum of -0.080 to -0.060 MPa for 15-30 minutes, then restore it to normal pressure. Adjust the pH of the system to 8.0-8.6 using a 10% sodium hydroxide aqueous solution. Place the pH-adjusted system in a sealed reaction vessel and react it at 52-58°C and 150-300 r / min for 5-8 hours. S5. After the reaction is complete, the resin particles are obtained by vacuum filtration. The resin particles are transferred to a washing column and washed with deionized water at a flow rate of 2-4 BV / h until the pH of the washing solution is 6.5-7.5 and the absorbance of the washing solution at 280 nm is not greater than 0.
05. The washed resin particles are then vacuum dried at 40-50℃ and a vacuum degree of -0.080 to -0.060 MPa until the water content of the resin particles is 45%-58%, thus obtaining the modified resin. The total amount of added deionized water is 220 to 320 parts, excluding the water contained in silica sol, acetic acid aqueous solution, and sodium hydroxide aqueous solution.
3. The regenerable composite adsorbent for iron removal from amino acid mother liquor according to claim 1, characterized in that, The matrix of the D418 type resin is a styrene-divinylbenzene crosslinked copolymer, and the functional group is -NHCH2PO3Na2; the wet particle size of the D418 type resin is 0.315~1.25mm, the water content is 55%~60%, and the wet volume exchange capacity is expressed as Ca 2+ The concentration should be no less than 0.35 mmol / mL, the wet true density should be 1.10–1.18 g / mL, and the sphericity after grinding should be no less than 90%. The macroporous acrylate polar adsorption resin has a wet particle size of 0.40–1.00 mm, a specific surface area of 350–600 m² / g, and an average pore size of 8–25 nm. The acid-washed coconut shell granular activated carbon has a particle size of 0.45–1.20 mm, an iodine adsorption value of not less than 900 mg / g, an ash content of not more than 3.0%, and an iron content of not more than 0.02%. The carboxymethyl chitosan has a degree of carboxymethyl substitution of 0.65–0.95 and a degree of deacetylation of 80%–95%. The branched polyethyleneimine has a weight-average molecular weight of 10,000 to 30,000 Da; The silica sol has a silica mass fraction of 25% to 35% and a silica particle size of 8 to 25 nm.
4. The regenerable composite adsorbent for iron removal from amino acid mother liquor according to claim 1, characterized in that, The modified resin has a wet particle size of 0.40-1.00 mm accounting for no less than 95% of the total particle mass, a wet bulk density of 0.72-0.88 g / mL, and a sphericity of no less than 90% after grinding.
5. A method for preparing a regenerable composite adsorbent for iron removal from amino acid mother liquor according to any one of claims 1 to 4, characterized in that, Includes the following steps: The modified resin, D418 type resin, and macroporous acrylate polar adsorption resin were soaked in water for 8-12 hours, and the acid-washed coconut shell granular activated carbon was soaked for 2-4 hours. After soaking, the components were filtered under reduced pressure to remove free water. After filtration, the above components were added to a mixing device and mixed to obtain a regenerable composite adsorbent.
6. A method for removing iron from amino acid mother liquor using a regenerable composite adsorbent prepared according to any one of claims 1 to 4 or the preparation method described in claim 5, characterized in that, Includes the following steps: A1. The renewable composite adsorbent is mixed with deionized water to form a slurry, and then wet-packed into the adsorption column. A2. The amino acid mother liquor is transported to a microfiltration device and circulated microfiltration is carried out under the conditions of 20-45℃, transmembrane pressure difference of 0.08-0.25MPa, and membrane surface flow rate of 1.0-3.0m / s until the mass fraction of suspended solids with a particle size greater than 10μm in the permeate is no higher than 0.01%. Microfiltration is then stopped to obtain the pretreated mother liquor. A3. Adjust the pH of the pretreated mother liquor to 4.2-5.5 and the temperature to 25-40°C. Pass the solution into the adsorption column filled with the regenerable composite adsorbent from the bottom of the adsorption column and perform upward adsorption treatment at a flow rate of 2.5-3.0 BV / h. A4. After the liquid starts to flow out from the outlet of the adsorption column, collect the replacement liquid from the front section separately. When the total free amino acid concentration in the effluent reaches more than 95% of the total free amino acid concentration in the feed mother liquor, the low-iron treatment liquid determination stage begins; the soluble total iron content in the effluent is tested periodically or continuously, and the effluent with a soluble total iron content not exceeding 5 mg / L is collected as the low-iron treatment liquid. When the total soluble iron content in the effluent first exceeds 5 mg / L, feed is stopped, and the effluent corresponding to this test is collected separately from the low-iron treatment solution.
7. The method according to claim 6, characterized in that, The total soluble iron content of the amino acid mother liquor before treatment is 100-300 mg / L; The microfiltration device has a filtration accuracy of 5–10 μm.
8. The method according to claim 6, characterized in that, In a state of no liquid flow, the regenerable composite adsorbent packed in the adsorption column forms a static bed. The ratio of the height of the static bed of the regenerable composite adsorbent in the adsorption column to the inner diameter of the adsorption column is 3:1 to 8:1, and the height of the free space above the bed is 25% to 45% of the height of the static bed.
9. The method according to claim 6, characterized in that, After step A4, the following regeneration steps are also included: A5. While keeping the adsorbent bed submerged in liquid, drain the residual amino acid mother liquor from the adsorption column and replace the residual liquid with 0.5–1.0 BV of deionized water at a flow rate of 1.0–1.5 BV / h. A6. Acid wash with 3.0 BV of 5.0% hydrochloric acid aqueous solution at a flow rate of 3.0 BV / h from the top of the adsorption column. After the acid wash is completed, let it stand for 20-40 minutes. A7. Pass deionized water through the top of the adsorption column at a flow rate of 2.0 to 3.0 BV / h until the pH of the outlet liquid of the adsorption column is greater than 4.
0. A8. A 3.0 BV, 5.0% sodium hydroxide aqueous solution was introduced from the top of the adsorption column at a flow rate of 3.0 BV / h for alkaline washing. After the introduction was completed, the column was allowed to stand for 20-40 minutes. A9. Deionized water is introduced from the top of the adsorption column at a flow rate of 2.0 to 3.0 BV / h. The pH and conductivity of the adsorption column outlet liquid are measured until the pH of the adsorption column outlet liquid is less than 10.0 and the absolute value of the difference between the conductivity of two consecutive 0.5 BV outlet liquids is not greater than 5% compared with the conductivity value of the previous 0.5 BV outlet liquid. The regeneration of the regenerable composite adsorbent is then completed. A10. Introduce conditioning water with a pH of 4.2 to 5.5 from the bottom of the adsorption column at a flow rate of 1.0 to 1.5 BV / h until the pH of the outlet liquid of the adsorption column is 4.2 to 5.5, thus completing the bed conditioning.
10. The method according to claim 9, characterized in that, After completing the regeneration operations described in steps A5 to A9 and the bed conditioning in step A10, the regenerable composite adsorbent is reused for the adsorption treatment in step A3.